2014
DOI: 10.4236/ojrad.2014.41018
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MR Imaging of the Benign Hepatic Focal Lesions

Abstract: A. El-Badrawy et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…In the present study, out of 40 cases, maximum number of cases were in age group of 41-60 years .Malignant lesions showed male preponderance with male to female ratio of 1.8:1 and benign lesions showed female preponderance with male to female ratio of 0.7:1,as similar to that reported in previous studies. [7][8][9][10] more number of lesions were found in right lobe of liver than left lobe, Similar to existing studies. [7,10] Out of all lesions maximum were malignant, positive correlation was seen with other studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, out of 40 cases, maximum number of cases were in age group of 41-60 years .Malignant lesions showed male preponderance with male to female ratio of 1.8:1 and benign lesions showed female preponderance with male to female ratio of 0.7:1,as similar to that reported in previous studies. [7][8][9][10] more number of lesions were found in right lobe of liver than left lobe, Similar to existing studies. [7,10] Out of all lesions maximum were malignant, positive correlation was seen with other studies.…”
Section: Discussionsupporting
confidence: 80%
“…[7,10] Out of all lesions maximum were malignant, positive correlation was seen with other studies. [8,9] which also showed predominance of malignant lesions. In the present study the number of patients having single lesion was equal to number of patients having multiple lesions and there was no predominance of either groups.…”
Section: Discussionmentioning
confidence: 91%
“…However, there are some studies that reported similar ADC values of solid benign lesions (focal nodular hyperplasia and adenomas) and malignant lesions (metastases, hepatocellular carcinoma) [21,22]. Mean ADC values reported in this study are lower than what is reported in some previous studies [22,23].Variability in ADC values reported in studies is probably due to imaging parameters such as b-value selection or different techniques for respiratory compensation, either breath-hold or respiratory triggering [24]. In this investigation, the respiratory-triggered technique has been chosen for breathing compensation.…”
Section: Discussioncontrasting
confidence: 50%
“…Conventional diffusion-weighted imaging (DWI) has been widely reported to be useful in hepatic magnetic resonance imaging (MRI) for tumor detection and differentiation and the evaluation of infections, 1,2 yet it requires significant time for the imaging process. Although many imaging methods, such as long echo-train imaging, parallel imaging, and compressed sensing have significantly reduced the acquisition time, 3 general DWI is based on spin-echo T2-weighted or echo-planar imaging, which requires a sufficiently long TR 4 .…”
mentioning
confidence: 99%